A Forefoot Strike Requires the Highest Forces Applied to the Foot Among Foot Strike Patterns - Hashizume, Satoru; Yanagiya, Toshio (Sports Medicine International Open, 2017)
Ground reaction force is often used to predict the potential risk of injuries but may not coincide with the forces applied to commonly injured regions of the foot. This study examined the forces applied to the foot, and the associated moment arms made by three foot strike patterns. 10 male runners ran barefoot along a runway at 3.3 m/s using forefoot, midfoot, and rearfoot strikes. The Achilles tendon and ground reaction force moment arms represented the shortest distance between the ankle joint axis and the line of action of each force. The Achilles tendon and joint reaction forces were calculated by solving equations of foot motion. The Achilles tendon and joint reaction forces were greatest for the forefoot strike (2 194 and 3 137 N), followed by the midfoot strike (1 929 and 2 853 N), and the rearfoot strike (1 526 and 2 394 N). The ground reaction force moment arm was greater for the forefoot strike than for the other foot strikes, and was greater for the midfoot strike than for the rearfoot strike. Meanwhile, there were no differences in the Achilles tendon moment arm among all foot strikes. These differences were attributed mainly to differences in the ground reaction force moment arm among the three foot strike patterns.
Keywords: running; moment arm; Achilles tendon force; joint reaction force; musculoskeletal injury